Green synthesis of anisotropic zinc oxide nanoparticles with antibacterial and cytofriendly properties. (February 2018) - Saravanan, M.; Gopinath, V.; Chaurasia, Mukesh Kumar; Syed, Asad; Ameen, Fuad; Purushothaman, N.
Abstract: Zinc oxide nanoparticles (ZnONPs) exhibit abundant biomedical applications. Anisotropic ZnONPs with a defined shape and size were synthesized using Bacillus megaterium (NCIM 2326) cell free extract as a bio-reductant. The study investigated the multidimensional effect of ZnONPs on Helicobacter pylori strains and assessed its biosafety in normal human mesenchymal stem cells (hMSc). The highly stable ZnONPs were produced using B. megaterium and Zinc nitrate as a precursor. The phase of ZnONPs formation and structural characterization were performed by UV- visible (UV-Vis), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) and Field Emission Scanning electron microscopy (FESEM) analysis. Furthermore, the ZnONPs exhibited higher biocompatibility against human mesenchymal stem cells (hMSC) and proved to be potentially safe in mammalian cells. Corroborating the current investigation, we described the anti- H. Pylori dosage of ZnONPs was safe to hMSC and could efficiently use as nano-antibiotic. Graphical abstract: Image 1 Highlights: Development of anisotropic ZnONPs using Bacillus megaterium . ZnONPs characterized by high throughput analytical techniques UV-Vis, XRD, FESEM and FTIR spectrum. Significant antibacterial efficacy against Helicobacter pylori was observed for ZnONPs. Biocompatibility of ZnONPs was established on human mesenchymal stem cells.